Origin of the formation of isostructural bcc-Fe+bcc-Cu nanocomposites in Fe–Cu alloy via vacuum co-deposition - A. I. Ustinov; L. O. Olikhovska; S. O. Demchenkov; V. S. Skorodzievskii; S. S. Polishchuk; T. V. Melnychenko (AIP Advances)
This study examined the influence of substrate temperature and the ratio of iron and copper vapor flow on the structural state of Fe–Cu vacuum condensates. XRD patterns of the condensates deposited under specific electron beam physical vapor deposition process parameters revealed peaks corresponding to either bcc or bcc+fcc phases. Analysis of the lattice parameter of the single bcc structure indicates that only a portion of the copper atoms dissolve in the bcc-Fe lattice, while undissolved copper atoms form bcc-Cu inclusions that are coherent with the bcc-Fe lattice. A model for the formation of the bcc-Cu structure as an adaptive phase is proposed. The formation of the adaptive phase in vacuum condensates is driven by the bcc-Cu epitaxy on the surface of bcc-Fe crystallites and excess vacancies in the condensate structure. As the copper concentration in the isostructural Fe–Cu composite increases, the level of microstrain in its bcc crystal lattice also increases. The transformation of bcc-Cu particles into fcc-Cu via a shear mechanism occurs when heated above 400 °C. It was found that increasing the deposition temperature reduces the concentration range for the formation of the isostructural composite. It is suggested that higher deposition temperatures and increased copper concentration lead to larger copper particle sizes and reduced excess vacancy concentration, which disrupts their coherence with the bcc-Fe matrix. As a result, a composite with a eutectic-like microstructure consisting of bcc-Fe and fcc-Cu phases forms directly during vapor phase condensation.